AN EXPLORATORY INVESTIGATION ON TEACHING ARABICS WRITING THROUGH OUTDOOR CLASS - Hamidah, Hamidah; Ahmadi, Ahmadi; Mubarak, Mahfuz Rizqi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
This study aimed to explore the preparation of an outdoor study, the experiences of students and the results of their essays after doing an outdoor study using the exploration method of 14 students. The techniques used were interviews and analysis of their written documents. The findings of this study indicated that outdoor study activities began with preparation to achieve learning objectives by setting a schedule of activities. Students felt that outdoor study activities in learning to write made it easier for them to write based on the realities of people's lives without having to imagine as well as being able to socialize with the community. Students' essays were generally seen from the aspects of content, content organization, vocabulary and grammar in general according to facts, good and precise. There were three topics written about the function of the Kereng Bangkirai Pier and the title of the essay and the flow of the different descriptions. The implication of this research is that learning in an environment that matches the theme of the material helps students in developing their competences from cognitive, affective and psychomotor aspects.